Gender differences in operational and cognitive abilities - Lager, Emil; Sorjonen, Kimmo; Melin, Marika (Frontiers in Psychology, 2024)
Introduction Gender differences in cognitive and operational abilities have been identified. Yet, their interrelationship remains underexplored. This prevents tailored evidence-based selection, allowing discrimination to persist. Methods Data from a test battery of operational and cognitive tests was analyzed. In total 2,743 aviation pilot candidates’ test scores were analyzed. Results Males had a significantly higher score on mental spatial ability, memory retention, abstract problem solving, multitasking ability (MU), and manual spatial ability (MSA); and females on perceptual speed. Correlations between MU and MSA [difference = 0.269 (95% CI: 0.114; 0.405)] and between MSA and perceptual speed [difference = 0.186 (95% CI: 0.027; 0.332)] were significantly stronger among female applicants. A high MSA score was more predictive of a high score on MU, Perceptual speed, and Memory for female compared with male applicants (p < 0.002 for the MSA score × sex interaction effect in all three cases). Discussion Interpretation of test scores in between genders potentially may need to look different for final selection decisions for operational professions, as female test profiles were shown to exhibit greater homogeneity.